Through the eyes of serial killers: interviews with seven murderers - Fezzani, Nadia (Dundurn, 2015)
Nadia Fezzani conducted groundbreaking, uncensored interviews with multiple-murderers behind bars. The account she pieces together from interviews, psychological research, criminal profiling, and genetic studies, is as unsettling as it is undeniable. The scars of abuse, and cold-blooded logic all emerge as Fezzani dissects serial killers' personalities in a quest to understand those who have committed unthinkable crimes